An Archeological Survey of the Cross Ditch No.2 and Central Ditch Cleanout Project Poinsett County, Arkansas - Taylor, Robert A.; Spears, Carol S. (1986)
An intensive cultural resource survey with initial site testing was conducted by Spears Professional Environmental and Archeological Research Service (SPEARS) for the U. S. Army, Corps of Engineers, Memphis District. The surveyed area consisted of about 1.5 miles of ditch corridor along Cross Ditch No. 2 and Central Ditch in the St. Francis Floodway levee system of Poinsett County. One previously unrecorded site, designated as 3PO492, was found. Controlled surface collections were performed at the site and the diagnostic artifacts included: one human tooth (molar); shell, sand, and clay tempered pottery; one Nodena arrowpoint; and 2 Weems projectile points. Initial testing consisting of the excavation of one 1m x 1m unit indicated that intact deposits lay buried beneath a 15 cm plowzone and a 10 cm sterile clay band. This site had been bisected by the Cross Ditch No. 2 and artifacts removed in ditch construction were found in the plowzone and/or on the surface of fields on both sides of the ditch. Datable artifacts indicate that the site dates to the Woodland and Mississippian Periods, with evidence of the Tchula (Early Woodland) , the Cherry Valley (Middle Mississippian), and the Parkin (Late Mississippian) phases represented in the assemblage. 3PO492 contains information related to lithic and ceramic technology, human biophysical remains, faunal and floral resources. The site is eligible for nomination to the National Register of Historic Places. Testing is recommended to determine subsurface boundaries and the potential construction impacts of the proposed project to characteristics which lend significance to the site.